Discretion and Strategies for Investigating Child Abuse: Social Workers’ Conceptions of Child Abuse Investigations and Police Reporting - Quarles van Ufford, Sara; Heimer, Maria; Schön, Ulla-Karin; Linell, Hanna (The British journal of social work, 2024)
Understanding the capacity of child welfare (CW) organisations to deal with child abuse is complex, and dependent on the specific CW context. Sweden occupies a unique position in trying to balance high demands for CW and protection with a strong family support focus, which carries a risk of overlooking children who need protection. Drawing on an understanding of social service organisations as street-level bureaucracies, this article explores discretion in child abuse cases by examining conditions affecting discretion and strategies for investigating child abuse, including police reporting. Thematic analysis of interviews with Swedish supervising social workers showed that staff’s conceptions of the CW system influenced the exercise of discretion, leading to different strategies for dealing with child abuse. This resulted in different practices and potentially unequal access to child protection and support, highlighting the wide margin of discretion. This article concludes that the interplay between knowledge and governance is central to equal child protection. This article contributes to the discussion of discretion in CW organisations by underlining the importance of being particularly vigilant about discretion when both children and parents are considered clients, as the child risks being lost as a subject with individual needs and rights. Understanding the capacity of child welfare (CW) organisations to deal with child abuse is complex. Sweden occupies a unique position in trying to balance high demands for CW and protection with a strong family support focus, which carries a risk of overlooking children in need of protection. This article explores the handling of child abuse cases by examining conditions affecting discretion and strategies for investigating child abuse, including police reporting. Analysis of interviews with Swedish supervising social workers showed that staff’s conceptions of the CW system influenced the handling, leading to different strategies for dealing with child abuse. This resulted in different practices and potentially unequal access to child protection and support, underscoring the importance of being particularly vigilant about discretion when both children and parents are considered clients: the child risks being lost as a subject with individual needs and rights. This article concludes that the interplay between knowledge and governance is central to equal child protection.